Elastic melt-blown nonwoven fabrication of styrene‐ethylene/butylene‐styrene copolymer and polypropylene blends: a study of morphology and properties. Issue 9 (May 2022) - Chang, Li; Wu, Chuanfen; Lan, Pengfei; Bai, Bing; Jiang, Liang; Chen, Shaojuan; Jerrams, Stephen; Ma, Jianwei
Fabrics produced by the melt-blown nonwoven process have the advantage over competing materials of possessing an ultrafine fibrous and porous structure. However, their brittleness and poor toughness restrict their wider application. There is increasing demand for nonwovens that have high stretchability and elasticity while maintaining a melt-blown structure. In this study, polypropylene (PP) and styrene‐ethylene/butylene‐styrene copolymer (SEBS) were blended at different ratios and subsequently used in the melt-blowing process. The morphology of the blends displayed a co-continuous structure when the ratio of SEBS to PP in blends was similar. Furthermore, it was found that all the blends had good spinnability from the melt-blowing process during rheological and thermal properties tests. All the elastic melt-blown nonwovens fabricated in this research had elongations higher than 400% and elastic recoveries higher than 50%, which was indicative of good elasticity. Meanwhile, the nonwovens maintained fine fiber diameters and good filtration properties, in keeping with traditional melt-blown nonwovens.